The Impact of Consumer Satisfaction on Consumer Loyalty in the Honey Industry (A Study of Suhita Honey and Similar Products) - Edy Humaidi; Bina Unteawati; Kusmaria Kusmaria (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Honey is a product that is much sought after by consumers as a health product. So far, honey producers have only focused on increasing consumer confidence that their product is genuine honey without worrying about consumer satisfaction, making it challenging to attract loyal consumers. This study aims to analyze the influence of consumer satisfaction on consumer loyalty to Suhita Honey. This study was conducted using interviews and direct observation. Sampling Method This survey was taken as an accidental sample from a total sample of 34 respondents. The techniques used are descriptive analysis and structural equation model (SEM) analysis. The results showed a significant influence between customer satisfaction and loyalty with the Suhita brand, with a P-value of 0.000 (<0.05) and an R-squared value of 0.897, representing 89% of the variables in this study were customer satisfaction. This can explain the variable of consumer loyalty. Other variables outside this research model explain the rest.